Oral ulcer activity in Behcet's disease: Poor medication adherence is an underestimated risk factor - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (AVES, 2017)
Objective: The aim of this study was to evaluate the relationship between oral ulcer activity and medication adherence according to gender in Behcet's disease (BD) patients. Material and Methods: The study group included 330 BD patients (F/M: 167/163, mean age: 38.5 +/- 10.5 years). Oral ulcer activity and medication adherence were evaluated in the previous month. Medication adherence was evaluated using the 8-item Morisky Medication Adherence Scale (MMAS-8) having a score range of 0 to 8 with high scores indicating better adherence. Low adherence was defined as < 6 points on MMAS-8. Results: Over half of the group had active oral ulcers (n= 219, 66.4%) within the month preceding the visit. The number of oral ulcers was significantly higher in female patients with low medication adherence (2.39 +/- 3.24) than in the rest of the female group (1.28 +/- 2.05; p= 0.023). Although a similar trend was also observed in male patients (2.14 +/- 3.3 vs. 1.81 +/- 2.31), a significant relationship was not observed (p= 0.89). The frequency of medication intake per day was lower in patients with high medication adherence than in the rest of the study group (p= 0.04). Conclusion: Low medication adherence is a hidden risk factor in the management of BD. Poor adherence was associated with oral ulcer activity in female BD patients.
Keywords: Medication adherence; oral ulcer; Behcet's disease; CROSS-CULTURAL ADAPTATION; RHEUMATOID-ARTHRITIS; PREDICTIVE-VALIDITY; NONADHERENCE; MANAGEMENT; QUESTIONNAIRE; COLCHICINE